The Production of Translated Texts for Migrant Minority Communities. Some Characteristics of an Incipient Market - Sales-Salvador, Dora; Valero-Garcés, Carmen (The Journal of Specialised Translation, 2007)
The production of translated texts for migrant minority communities which are culturally and linguistically differentiated is a requested way of communication nowadays. This study is devoted to translation for migrant communities in Spain, a country which is experiencing deep changes regarding both the structure of societies and the forms of establishing relationships between people. A quick continuous increase in the flow of people from Africa, Eastern Europe, and Asia is forcing government and non-governmental organisations (NGO) somehow related with migrants to develop initiatives to overcome a wide range of barriers (linguistic, socio-cultural, political, economic, and so on). The production of multilingual texts is an incipient reality. First, a brief introduction regarding the translation into minority languages and cultures will be provided; second, a tentative classification of the types of texts typically translated will be presented; and third, some characteristics of the materials translated will be analysed. Finally, we will posit some general conclusions and suggestions for further research on the nature of translation as socio-cultural practice in public services.